PENGEMBANGAN MEDIA PEMBELAJARAN MAKE A MATCH CARD BERBASIS QR CODE PADA PEMBELAJARAN IPAS KELAS IV SD TOPIK BAGIAN TUBUH TUMBUHAN - Virnanda Dualis Tanto; Nanang Khoirul Umam; Arya Setya Nugroho (Nusantara Hasana Journal, 2024)
In the era of Industrial Revolution 4.0, the education system is expected to be able to realize that students have skills that are able to think critically and solve problems, be creative and innovative as well as communication and collaboration skills. Also skills in searching, managing and conveying information as well as skills in using information and technology. One media that can attract students is the QR code-based make a match card game. So the researcher wishes to conduct a research entitled "Development of Learning Media. Development of Make a match card Learning Media Based on QR code in Class IV Elementary School Science Learning, Topic of Plant Body Parts". This research uses Development research (4 D). This research aims to produce products with valid, practical and effective quality. The product developed in this research is QR code-based learning media on plant content, the source of life on earth, the topic of plant body parts in class IV elementary school. The research and development model used in this research is the 4D model proposed by Thiagarajan (in Trianto, 2010:93) with the steps of defining, designing, developing and disseminating.